Enhanced thermal and mechanical properties of PW‐based HTPB binder using polystyrene (PS) and PS–SiO2 microencapsulated paraffin wax (MePW). Issue 18 (17th January 2018) - Gao, Xia; Zhao, Tianbo; Luo, Guan; Zheng, Baohui; Huang, Hui; Ma, Rui; Han, Xue; Chai, Yuqiao
ABSTRACT: Polystyrene (PS) microencapsulated paraffin wax (MePW) and PS–SiO2 MePW were used to improve the form‐stability of PW in hydroxyl‐terminated polybutadiene‐derived polyurethane (HTPB) binder. HTPB matrix containing different contents of PS MePW, PS–SiO2 MePW, and PW were prepared. The chemical composition, crystallinity, microstructure, heat capacities, thermal stabilities, thermal reliabilities, leakage, and mechanical properties of the composites were compared using Fourier transforms infrared spectroscope, X‐ray diffractometer, scanning electronic microscope, differential scanning calorimeter, thermo‐gravimetric analyzer, thermal cycling test, leaking test, compression, and tensile tests, respectively. The results showed that the MePW/PW/HTPB composites were prepared without chemical reaction. The thermal stability and mechanical properties of PS–SiO2 MePW/PW/HTPB increased more dramatically than that of PS MePW/PW/HTPB. With the increasing contents of MePWs, the PW leakage of the composites decreased, especially for PS MePW/PW/HTPB. Consequently, the MePW/PW/HTPB composites possess a potential application for PW‐based polymer‐bonded explosive system. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46222. Abstract :